los proyectos educativos para la conservación del ambiente con estudiantes de cuarto semestre de la carrera de biología, química y laboratorio, período septiembre 2016 – marzo 2017 - Ñauñay Quishpe, María Fernanda (2017)
The investigation is orientated to explain if the educational projects like methodological strategy help to sensitize to the care and conservation of the environment in the students of fourth semester of Biology, Chemistry and Laboratory School during the period September, 2016 – March 2017. It was detected that the teachers occasionally use educational projects as methodological strategy. John Dewey considers that the learning experiential is an alternative to answer to the problems of education. At the same time, experiential learning leads to the student active participation developing was based on the not experimental design, documentary and field type, the level is diagnostic and descriptive. For the compilation of the information survey with its instrument, the questionnaire, were applied to a population of 18 students. It was conclude that the students are conscious of the environmental problems affecting the planet. It is recommended to apply methodological active strategies as the educational projects that orientate the student to mitigate the climate change and to diminish the possible consequences